Inflammation and Blood Clotting Case for First-Year Medical Students - Team-Based Learning Format - Maria Sheakley; Phil Conran; Mary Moore; Agnes LaVille (Association of American Medical Colleges, 2009)
Abstract Introduction This resource is a team-based learning module on inflammation and blood clotting for first-year medical students. After using this resource, students will be able to describe the signs and symptoms of inflammation, identify histological sections of inflamed tissue, and discuss the underlying cellular mechanisms responsible for inflammation. In addition, students will be able to discuss the process of blood clotting, including the factors involved in the intrinsic and extrinsic coagulation cascades. Finally, students will be able to describe and distinguish between the clinical tests used for diagnosis of clotting disorders. Methods Team-based learning cases utilize a specific written format and method of facilitating to produce very effective small-group and class discussions. There is a detailed description of this process in the facilitator's version of the module. In our experience, the instructors of this case should be prepared to discuss specific blood-clotting disorders and the different diagnostic tests used to differentiate between them. Results We have used this case one time thus far, in a class of 70 students who were divided into 11 groups. The student feedback from this module was all positive. We found that the first three questions were fairly straight forward and most groups got the answers correct. There was more discussion about questions four and five, as these are the more clinically relevant questions and the students are not used to analyzing diagnostic tests at this point in their medical education. Discussion The most effective part of the case was the inclusion of questions that required students to think about the diagnostic tests used to diagnose blood clotting disorders. This stimulated great discussion and helped the students see the relevance of basic science education in the context of medicine.